2016
DOI: 10.15255/cabeq.2015.2281
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Fennel (Foeniculum vulgare) Seeds: Process Optimization and Antioxidant Capacity of the Extracts

Abstract: This paper presents the study on the extraction of bioactive substances from fennel seeds. The impact of the main process variables (solvent composition, liquid-to-solid ratio, temperature, contact time) on the concentration of the target substances (polyphenols and flavonoids) in the extracts is studied resulting in the selection of a set of operating parameters, at which their content is maximized. Extracts with higher concentration of target compounds demonstrate higher antioxidant capacity, which confirms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
(14 reference statements)
1
1
0
Order By: Relevance
“…Application of higher temperatures in MAE resulted in the increase in TPC, producing the highest yields at 80 • C. This trend can be related to the enhanced penetration of the solvent into the sample matrix at elevated temperatures, especially since fennel seeds have a firm structure, which makes the extraction process at lower temperatures less effective. Also, it can be observed that ethanolic extracts, which gave the lowest TPC values at lower extraction temperatures, reached a phenolic content comparable to acetone extracts at 80 • C. The increase in TPC and flavonoids content in fennel seeds extracts with temperature elevation was also observed in the study by Angelov and Boyadzhieva (2016) [40] and Repajić et al (2020) [41], where TPC values in fennel seeds were almost 45% higher at 110 • C than at 80 • C during pressurized liquid extraction. On the other hand, prolonged exposure to high temperatures may lead to degradation of phenolic compounds due to oxidation, decomposition and/or polymerization processes [14].…”
Section: Mae Optimizationsupporting
confidence: 73%
“…Application of higher temperatures in MAE resulted in the increase in TPC, producing the highest yields at 80 • C. This trend can be related to the enhanced penetration of the solvent into the sample matrix at elevated temperatures, especially since fennel seeds have a firm structure, which makes the extraction process at lower temperatures less effective. Also, it can be observed that ethanolic extracts, which gave the lowest TPC values at lower extraction temperatures, reached a phenolic content comparable to acetone extracts at 80 • C. The increase in TPC and flavonoids content in fennel seeds extracts with temperature elevation was also observed in the study by Angelov and Boyadzhieva (2016) [40] and Repajić et al (2020) [41], where TPC values in fennel seeds were almost 45% higher at 110 • C than at 80 • C during pressurized liquid extraction. On the other hand, prolonged exposure to high temperatures may lead to degradation of phenolic compounds due to oxidation, decomposition and/or polymerization processes [14].…”
Section: Mae Optimizationsupporting
confidence: 73%
“…Green synthesis of ZnO NPs was explained by the bioaccumulated metal ions and their involvement as reductants and stabilizers. 31 , 32 The change in color was attributed to zinc nitrate reduction in ZnO NPs. This change resulted in the excitation of surface Plasmon vibrations of the nanoparticles, which led to surface Plasmon resonance, 7 suggesting the nanoparticle’s FCC crystal structure.…”
Section: Resultsmentioning
confidence: 99%